PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP CUSTOMER LOYALTY MELALUI CUSTOMER SATISFACTION (STUDI PADA PELANGGAN GO-JEK DI KOTA PADANG) - Ayu Nur Aziza; Dessy Kurnia Sari (Politeknik Negeri Lhokseumawe, 2019)
This study aims to determine the influence of Customer Relationship Marketing Against Customer Loyalty Through Customer Satisfaction at Go-Jek customers in Padang City. The data analysis method used is structural equation modeling analysis with the help of Smart PLS 3.0 program. This study uses 135 respondents as a sample of research. The variable consists of three types of variables, namely the independent variable (X) is Customer Relationship Management, the dependent variable (Y) is Customer Loyalty and as the mediation variable (M) is Customer Satisfaction. The results of this study indicate that Customer Relationship Management has a positive and significant impact on Customer Satisfaction, Customer Satisfaction has a positive and significant impact on Customer Loyalty and Customer Satisfaction mediate some relationship between Customer Relationship Management to Customer Loyalty.Keywords: Customer Relationship Management, Customer Loyalty and Customer Satisfaction